Utilization of Home Yard Land to Meet Family Needs in Soya Village, Sirimau District, Ambon City - Rado, Priska; Salakory, Melianus; Sihasale, Daniel Anthoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Many human activities are carried out on land, such as settlements, agriculture, protected forests, and tourist destinations. Land is a natural resource that is very important to meet human needs and can be utilized in various ways. One common way of using land is through the yard, where the yard is used and processed with multiple methods to make it worthwhile. However, the problem that often occurs in using yard land is the need for more public understanding of the importance of utilizing yard land and the lack of government notification of the importance of using yard land to the community. Utilization of yard land in this context is the sustainability of food and the family economy in Soya Village. With the increasingly critical condition of agricultural land in Indonesia, the utilization of yard land at the household level is strategic and very relevant. Utilizing yard land provides opportunities for families with ample land, increases income, and provides high economic value to the land. The results of this study indicate that the utilization of yard land not only meets family needs but also has a positive impact on the household economy. The sustainability of land use can help overcome the problem of food availability and support the family economy. The research method involving direct interviews with respondents provides a better depth of information. Thus, this study can be a basis for further efforts in optimizing the use of yard land in Soya Village to improve food security and welfare for families who utilize their yard land.